The V617I Substitution in Avian Coronavirus IBV Spike Protein Plays a Crucial Role in Adaptation to Primary Chicken Kidney Cells - Jiang, Yi; Gao, Mingyan; Cheng, Xu; Yu, Yan; Shen, Xinyue; Li, Jianmei; Zhou, Sheng (Frontiers in Microbiology, 2020)
Almost all avian coronavirus infectious bronchitis virus (IBV) could not infect and replicate in the mammalian cells, which renders difficulty in studying the IBVs at the cellular level. A series of recombinant viruses were constructed by chimerizing the S genes of CK cell-adapted strain H120 and non-adapted strain IBYZ. The results showed that the S2 subunit determines the difference in cell tropism of the two strains. Then we compared the amino acid sequences of S protein of YZ120, a CK cell-adapted strain, with its parental strain IBYZ, and three mutations, A138V, L581F, and V617I, were identified. Using YZ120 as the backbone, one or more of the above-mentioned mutation sites were eliminated to verify the correlation between these sites and CK cell tropism. The results showed that the CK cell tropism of the YZ120 strain depends on the mutation of V617I, the change of L581F promotes the adaptation of the virus in CK cells, and the 138 position is not directly related to the CK cell tropism. Further validation experiments also showed that 617 has a decisive role in the adaptation of IBV to CK cells, but other areas of the virus skeleton also affect the replication efficiency of the virus in CK cells.